Healthcare Waste Generation and Management in Public Healthcare Facilities in Adama, Ethiopia - Hayleeyesus, Samuel Fekadu (J Health Pollut, 2016)
BACKGROUND. Over the past few years there has been rising production of hazardous byproducts, including dioxins, furans, and mercury from indiscriminate handling and treatment of healthcare waste. This situation is worse in developing countries where there is a serious lack of reliable data on factors such as generation and characteristics of healthcare waste. OBJECTIVES. To investigate healthcare waste generation and current management practices of public healthcare facilities in Adama, Ethiopia. METHODS. All departments and sections in studied healthcare facilities (one referral hospital and four health centers) were examined for the characterization and determination of healthcare waste generation based on World Health Organization (WHO) guidelines. Wastes were collected and measured daily for seven consecutive days. Plastic buckets and bags of different colors were used for different types of wastes. Plastic bags were removed every morning and their weights were measured every day at 8 am using a scale. RESULTS. The average daily generation of healthcare waste from studied health centers ranged from 0.02 to 0.03 kg/patient/day, and the average daily waste generation of Adama referral hospital was 1.23 kg/bed/day. The healthcare waste generation rate was statistically different across the health service delivery sectors (p < 0.001). The proportion of hazardous healthcare waste generated in Adama referral hospital and health centers was 34.9% and 75%, respectively. There was no segregation of healthcare waste by type at the point of generation or pre-treatment of infectious waste in the studied healthcare facilities. Open pit burning and single chamber incinerators were the most utilized final treatment methods. Furthermore, there was a low level of awareness about safe healthcare waste management. CONCLUSIONS. The overall findings of this study indicate that the proportion of hazardous healthcare waste generated from the studied healthcare facilities was above the threshold set by the WHO. There is a lack of proper waste management systems in all public healthcare facilities in Adama, Ethiopia. Awareness raising activities on proper healthcare waste management should be undertaken targeting all healthcare workers.